Load compensating responses of human abdominal muscles - Lansing, R. W. (1981)
1. We studied abdominal muscle responses to positive pressure loads applied suddenly to the external airway while subjects held a constant lung volume against steady pressure. The pre-loading holding pressure was 6 cm H(2)O, and the loading pressures were 6 or 12 cm H(2)O lasting for 2 sec. 2. Surface electromyograms (e.m.g.) were recorded over the internal oblique, external oblique, and rectus abdominis muscles. The latency and pattern of the e.m.g. reactions were studied by measuring the raw record for each loading trial, and by averaging the rectified e.m.g. for many trials. 3. No responses were obtained if subjects were instructed not to respond to the loads. When instructed and trained to maintain their pre-load position in spite of the load, a two-phase compensatory response was found. The initial response (phase I) was 100-300 msec in duration; it was followed by a continuous e.m.g. discharge (phase II) which continued to the offset of the pressure load. Subjects were also trained to make a single respiratory effort as quickly as possible after the load onset or after just an auditory stimulus. These were simple reaction time tasks of a traditional kind and the e.m.g. responses elicited were single, brief bursts. 4. For all subjects and experimental conditions the e.m.g. response of the internal oblique occurred first, followed by the external oblique and then the rectus abdominis. For the `maintain position' task, phase I latencies (internal oblique) averaged 66-90 msec for individual subjects, but for single trials with optimal conditions of practice and preparatory intervals these ranged from 42 to 110 msec with a third of the reactions occurring within 50-60 msec. 5. The latencies for reaction time responses to loading were about 6 msec shorter than the phase I latencies. The latency distributions for the two types of responses were similar, and both were affected to the same degree by practice, and changing the length and variability of the preparatory interval. Because of these similarities we suggest that the phase I reaction was a learned response of a `simple reaction time' type, and not comparable to late stretch reflexes such as the M2 of limb muscles. 6. Arm muscle responses to respiratory pressure changes were measured in three subjects under identical conditions used to obtain load reaction times of abdominal muscles. These simple reaction times averaged 61-71 msec, and ranged from 42 to 97 msec. Therefore very short proprioceptive reaction times are not peculiar to the respiratory system, or to load perturbations of the responding muscle. 7. Mechanical adjustments of airway pressure and lung volume in response to loading are first expressed at the mouth about 90 msec after abdominal muscle activity begins. In the `maintain position' task, the accuracy with which pressure and volume adjustments were made during the last 1.5 sec of the loading period approximated that reported in the literature for trained singers holding a tone using constant expiratory pressure.